Relationships between Macronutrient Intake, Iron Intake, Nutritional Status, and Sleep Quality with Menstrual Cycle of Adolescent Girls in State Senior High School 5 of South Tangerang - Tandy, Cut Athaya Artawana; Ismawati, Rita (Jurnal Ilmiah Wahana Pendidikan, 2023)
Adolescence is a transitional period from childhood to adulthood characterised by several changes, including puberty, one of which is the onset of menstruation in women. According to Riskesdas data from 2010, 11.7% of Indonesian teenagers aged 15 to 19 had irregular menstruation. The goal of this study was to look into the relationship between macronutrient intake, iron intake, nutritional status, sleep quality, and menstrual cycle in female adolescents at SMA Negeri 5 Tangerang Selatan. This is a quantitative study that employs an analytic observational design and a cross-sectional technique. Female students from SMAN 5 South Tangerang participated in this study. The proportionate stratified random sampling technique was utilized in this study, and a total of 88 students who met the criteria were acquired. The findings revealed a link between macronutrient intake (carbohydrates, protein, and fat), iron intake, nutritional status, and sleep quality and the menstrual cycle (p = 0.05). The study concluded that there is a link between macronutrient intake, iron intake, nutritional status, and sleep quality and the menstrual cycle of female adolescents at SMA Negeri 5 Tangerang Selatan. As a result, the authors propose that schools educate young women on the importance of reproductive health and the factors that can affect reproductive health.